791 RECURRENT HIATAL HERNIA A HIGH PREDICTOR OF PATHOLOGIC REFLUX AND NEED FOR REINTERVENTION. (17th September 2021) - Greenberg, Jacques; Reyes, Fernando Valle; Christianson, Blake; Margolis, Daniel; Thiesmeyer, Jessica; Edelmuth, Rodrigo; Egan, Caitlin; Finnerty, Brendan; Fahey, Thomas J; Zarnegar, Rasa
Abstract: : Anti-reflux surgery (ARS) has been postulated to have high failure rates, which may approach 50% depending upon hiatal hernia size. Most failures are thought to be related to wrap disruption or hiatal hernia recurrence. Recently, diaphragmatic mesh augmentation has been shown to reduce hiatal hernia recurrence. We aimed to determine factors that influence recurrence based on vigilant imaging and diagnostic pH studies, and the need for surgical reintervention. Methods: A prospectively maintained database of all patients undergoing index robotic ARS (including Hill, Nissen, Toupet, and Linx procedures) with Phasix ST ® mesh was queried. Between December 2016 and July 2020, 134 patients were identified of which 92 met inclusion criteria for post-operative barium esophagram performed at routine intervals (6, 12, or 24-months) or for recurrent symptoms. Median follow-up time was 11.4 months. Clinical characteristics, manometry, pH studies, as well as surgical approach was evaluated. Radiographic recurrences were then associated with endoscopic confirmation and rates of surgical re-intervention. Results: Radiographic recurrence >2 cm was noted in 9 (9.8%) patients, of which 44% were symptomatic, compared to 36% of those without radiographic recurrence (p = 0.620). Endoscopy confirmed recurrence in 67% of patients with radiographic recurrence versus 0% without (p = 0.001). When all radiographic recurrences, including those <2 cm, were evaluated, 17 (18%) were identified, of which 53% of patients were symptomatic. Endoscopic and pH studies confirmed recurrences in 75% and 71% of these patients, respectively. Overall reintervention rates were 23% in the setting of any radiographic recurrence versus 1.3% without (p = 0.001). Conclusion: Recurrence rates following robotic ARS and hiatal hernia repair with mesh augmentation appear low with nearly 1-year follow-up. Prior to surgical reintervention, endoscopic and pH studies are warranted to confirm symptomatic recurrence. Recurrent hiatal hernias, including those <2 cm, can lead to abnormal pH studies that merit reintervention at rates higher than those without evidence of recurrence. Longer term follow-up is required to optimally delineate true recurrence patterns.